Первые товарищи: [повесть] / Лидия Чарская ; [художник А. Кузьмин] - Чарская Лидия Алексеевна (Мировая книжка, 2012)
Экземпляры: Ф. 1 (20240117) / Инвентарный номер: 43799 / Цена: 198.00 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Ч-22 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1